Agronomic biofortification of cereals with micronutrients: A systematic review - Elgin Davis, D S; Jawahar, S; Ragavan, T; Gurusamy, A; Mohandas, S; Sivasakthivelan, P; Elankavi, S (Plant Science Today, 2025)
Micronutrient malnutrition is a global issue, particularly in developing regions of Asia and Africa, where a substantial portion of the population relies heavily on cereal grains as their staple food source. This deficiency arises due to an inadequate intake of essential micronutrients such as zinc and iron, in their daily diets. Biofortification offers a readily accessible and expedient solution for biofortifying cereal grains with these crucial micronutrients. This approach is particularly beneficial for the poorest rural communities. These populations often lack the means to afford mineral supplements or animal-derived products, which are typically richer sources of these micronutrients. From an agronomic biofortification perspective foliar application of zinc and iron fertilizers is considered more effective and requires lower quantities compared to soil application. For selenium (Se), both soil and foliar applications have been found to be effective with sodium selenate being more effective than selenite for soil applications. Even in scenarios where cultivars or genetically modified crops with inherently higher zinc and iron content in their grains are developed adequate fertilization with these micronutrients will still be necessary. Therefore, in the long run agronomic biofortification serves as a complementary approach to plant breeding and modern biotechnology aiming to increase the overall micronutrient content in the food supply. In this review, we will explore the synergistic role of agronomic biofortification alongside plant breeding and biotechnology, highlighting its potential to enhance the micronutrient density of staple crops and address global micronutrient malnutrition.